In situ deletions reveal regulatory components for expression of an intracellular immune receptor gene and its co‐expressed genes in Arabidopsis - Yu, Huiyun; Yang, Leiyun; Li, Zhan; Sun, Feng; Li, Bo; Guo, Shengsong; Wang, Yong-Fei; Zhou, Tong; Hua, Jian (Wiley, 2022)
Intracellular immune receptor nucleotide‐binding leucine‐rich repeats (NLRs) are highly regulated transcriptionally and post‐transcriptionally for balanced plant defense and growth. NLR genes often exist in gene clusters and are usually co‐expressed under various conditions. Despite intensive studies of the regulation of NLR proteins, cis‐acting elements for NLR gene induction, repression or co‐expression are largely unknown due to a larger than usual cis‐region for their expression regulation. Here we used the CRISPR/Cas9 genome editing technology to generate a series of in situ deletions at the endogenous location of an NLR gene SNC1 residing in the RPP5 gene cluster. These deletions that made in the wild type and the SNC1 constitutive expressing autoimmune mutant bon1 revealed both positive and negative cis‐acting elements for SNC1 expression. Two transcription factors that could bind to these elements were found to have an impact on the expression of SNC1. In addition, co‐expression of two genes with SNC1 in the same cluster is found to be mostly dependent on the SNC1 function. Therefore, SNC1 expression is under complex local regulation involving multiple cis‐elements and SNC1 itself is a critical regulator of gene expression of other NLR genes in the same gene cluster.